The impact of sleep quality on reported anxiety and fatigue among shift nurses: The mediating role of resilience - Xin-Ge Wang; Yan-Yan Luo; Shuan-Rong Li (Wolters Kluwer Medknow Publications, 2020)
Aims: The aim of this article is to explore the relation of sleep quality, anxiety status, fatigue level and psychological resilience among rotating-shift nurses, thus, to propose solutions and promote physical and psychological health of shift nurses. Methods: The cross-sectional survey was performed on 263 clinical nurses recruited from three tertiary hospitals of Xinxiang City, Henan Province, China from October 2017 to June 2018. The questionnaire survey was conducted using Pittsburgh Sleep Quality Index (PSQI) for measuring nurses' sleep quality, connor-davidson resilience scale (CD-RISC) for measuring their psychological resilience, self-rating anxiety scale (SAS) for measuring their anxiety status, and Fatigue-14 Scale for measuring their fatigue. The relationship among above indicators were analysed using Pearson correlation analysis. The mediating effect of psychological resilience on the process of sleep quality impacting anxiety and fatigue was analyzed using Wen's causual steps method and linear regression. Results: The mean CD-RISC score of shift nurses was 57.76 ± 11.90, which indicated that resilience level was at a medium level. The mean of PSQI, SAS and total fatigue score was (7.53 ± 2.83), (50.56 ± 9.57) and (7.81 ± 9.42), respectively. Resilience could negatively predict the anxiety state (β = -0.366, P < 0.01) and fatigue (β = -0.197, P < 0.01). Sleep quality could positively predict anxiety (β = 0.395, P < 0.01) and fatigue level (β = 0.495, P < 0.01) for shift nurses. The mediating effects of resilience upon sleep quality and anxiety or fatigue was 0.044 and 0.026, respectively. Conclusion: The resilience could fuel sleep quality and reduce the occurrence of negative emotion and fatigue among shift nurses.